Challenges in Online learning towards better learning environment: A Case study on Bachelor of Business Management (BBM) Online Degree Programme at University of Jaffna, Sri Lanka - Yogendrarajah, R. (12th International Tamil Internet Conference, University of Malaya, Kuala Lumpur, Malaysia., 2013)
Sri Lanka is one of the countries to provide free education. The number of higher education opportunities is available to the students. However, a student still has to consider various factors and face many challenges, such as the lack of seats in national universities. The total number of Universities in Sri Lanka is fifteen (15) and nine (9) other Institutions that come under the University Grants Commission (UGC). Nearly 100, 000 students qualify each year to enter the Universities in Sri Lanka out of this around fifteen (15) percentage gain admission to follow the degree programmes. Only a small number among the left outs manage to continue studies at the tertiary level while majority of them are left with no future prospects. Even, the opportunity available to do the higher studies externally is negligible. The government has become increasingly willing to introduce online learning to deliver cost effective, easily accessible and current education to all ages and social backgrounds, on this regards of time, cost and geographical constraints in recent years. In the modern time of education, the rapid growth of Information and Communication Technology (ICT) leads to tremendously dynamic changes in a variety of tools and technologies applied to the learning process. Online learning has become an omnipresent concept in the time of ICT education and has also been identified as a major mode of learning where learners are able to select the occasion, location and the phase of learning. The University of Jaffna offering to contribute to the development of higher studies in its own way has initiated steps towards the provision of opportunities for higher studies at least to a small section, in the Tamil medium and in this regards the Bachelor of Business Management (BBM) Online Degree Programme has been introduced as an online mode delivery system. Now three batches are going on and around 300 students have been enrolled for this programme but statistics show that drop out rates from online learning courses are much higher than from traditional classroom based courses. In this paper it is argued that one reason for this is that the introduction of online learning and a more student centred learning model involves a drastic shift for students who are brought up in very teacher-centred didactic educational cultures. This paper mainly focuses on challenges that were come across during the design, development and delivery stages of the BBM Online Degree programme at University of Jaffna, Sri Lanka. The Case study approach is used as the research methodology and semi structured interviews with students and subject matter experts and observations are used as the data collection techniques. Content analysis is used as the case analysis technique and results revealed the major challenges in online learning in perceptive Student support, Flexibility, Teaching and Learning Activities, Access, Academic confidence. In this paper these challenges will be discussed and solutions suggested. It is concluded that the solutions for these challenges lead to a better learning environment.
Keywords: On line learning; Challenges; Student Support; Flexibility; Teaching and Learning Activities; Better learning environment.